THE RELATIONSHIP BETWEEN BADMINTON PLAYING FREQUENCY AND ACADEMIC STRESS LEVELS IN STUDENTS - Joli Purwanto Dadilan; Abu Bakar; Ardiansyah Nur (JURNAL PENDIDIKAN GLASSER, 2025)
The increasing academic pressure on junior high school students often leads to elevated stress levels, which can negatively impact learning and mental health. This study aims to examine the relationship between the frequency of playing badminton and academic stress levels among students at SMP Negeri 2 Luwuk. A quantitative approach with a cross-sectional design was employed. Data were collected through closed-ended questionnaires distributed to 50 students from grades VII and VIII, and analyzed using Spearman correlation. The results showed a significant negative relationship between the frequency of playing badminton and academic stress levels (r = -0.622, p = 0.001), indicating that students who play badminton more frequently tend to experience lower academic stress. These findings highlight that physical activity such as badminton can serve as an effective non-pharmacological preventive strategy for managing academic stress. The study suggests that integrating sports activities into school programs is essential to support students’ mental well-being. Future research is encouraged to adopt a longitudinal design and consider additional variables that influence student stress.